KARAKTERISTIK SPESIES FAUNA EKOSISTEM MANGROVE DENGAN METODE SURVEI DI KAWASAN TELUK BUNGUS – PADANG - Dwi Marsiska Driptufany; Fajrin Fajrin; Henny Yulius; Muhammad Hidayat; Eni Kamal; Aprizon Putra; Abdul Razak (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Mangrove ecosystems provide a variety of ecosystem services, including coastal protection, carbon sequestration, and opportunities for biodiversity. The mangrove ecosystem, which is an intermediate area between sea and land, has a sharp environmental characteristic gradient. The tides of seawater can cause large fluctuations in several environmental factors, especially temperature and salinity so that the animals that survive and thrive in the mangrove ecosystem are animals that have a great tolerance to extreme changes in environmental factors. This study aims to determine and identify the diversity of fauna species in the mangrove ecosystem. The survey location in this study is in the mangrove area of ​​Bungus Bay which is spread over 4 observation points, namely location 1 (Cindakir), location 2 (Kaluang Cove), location 3 (Kabung Labuhan Cino Cove), and location 4 (Pandan Cove) which is mangrove ecosystem as a sub-system of the coastal ecosystem. Based on the results of the field survey, there were no endemic species found in the protected zone on the coast of Bungus Bay. The fauna found in the mangrove ecosystem in the Bungus Bay area is divided into 2 (two) fauna characteristics, namely vertebrates consisting of 5 (five) species, namely aves (birds), reptiles, amphibians, mammals and primates and fish vertebrates. While invertebrates consist of Crustaceans or crabs, carideas or shrimp, molluscs, echinoderms, and polychaeta or worms. The results of the field survey showed that the types of species based on the family characteristics of the fauna found in the mangrove ecosystem at observation location 1 (Cindakir) were less than the number of species found at observation locations 2, 3 and 4 (Kaluang Cove, Kabung Labuhan Cino Cove, and Pandan Cove).